Laseracupuntura pulsada (frequência “E” de Nogier)aplicada nos pontos do eletrodiagnóstico energético paraintensidade da dor e qualidade de vida na síndrome fibromiálgica:ensaio clínico randomizado-estudo piloto. - Lima, Rosana Aparecida De (2021)
Fibromyalgia (FM) is considered a chronic disease that causes symptoms such as pain, sleep disorders, fatigue, morning stiffness and other associated symptoms such as paresthesia, headache, irritable bowel and anxiety, thus reducing quality of life. Among the treatments for these symptoms, Laseracupuncture can be highlighted, many studies address an intervention protocol, not identifying individualism. Because of this, the objective of this study was to analyze the effect of AT (Nogier's “E” frequency), applied at the points of energy electrodiagnosis, on pain threshold and quality of life (QL) in fibromyalgia syndrome. Method: the study was characterized as a randomized controlled clinical trial. The sample consisted of 20 volunteers diagnosed with Fibromyalgia. The sample was randomized with allocation into two groups: control group (CG - n=10) – received an educational lecture and experimental group (GEXP - n=10) – received treatment with AT. Treatment was carried out twice a week for three weeks. The assessment instruments were the Numerical Rating Scale (NEC), the 2010 American College Diagnostic Criteria, Fibromyalgia Impact Questionnaire (FIQ). Statistical tests were delta test, Shapiro-Wilk test, Mann-Withney test, Fridman test and wilcoxon test. The results show a significant reduction between groups for variable ECN (p<0.05), IDG (p<0.05), ESS (p<0.05) and FIQ (p<0.05). Conclusion: AT (Nogier's “E” frequency) applied to energy electrodiagnostic points had a positive effect on pain threshold and quality of life for fibromyalgia syndrome.